The aesthetics of Wabi-Sabi beautiful imperfection - Garcia, Leni (International Journal of Philosophy, 2015)
This paper puts forward Wabi-Sabi aesthetics as one possible philosophical anchor for museum exhibits that focus less on beauty as perfection and more on beauty that reveals the imperfect nature of life and serves as guide to joyful living. There is a growing trend in contemporary museums to feature not the usual paintings and sculptures, but crafts -traditionally looked upon as objects for the hobbyist, not the artist. The mixed reactions from the art world show that this new practice requires a philosophy of beauty that, to begin with, did not look for the beautiful in which is perfect as inspired by the Platonic ideals. The philosophy of Wabi-Sabis founded on the metaphysiscs of Budhism, is here offered as one such foundation, questioning the idea of beauty and art, and blurring the distinctions between art and life, as well as between art and crafts.